2010
DOI: 10.1371/journal.pcbi.1000920
|View full text |Cite
|
Sign up to set email alerts
|

Latent Factor Analysis to Discover Pathway-Associated Putative Segmental Aneuploidies in Human Cancers

Abstract: Tumor microenvironmental stresses, such as hypoxia and lactic acidosis, play important roles in tumor progression. Although gene signatures reflecting the influence of these stresses are powerful approaches to link expression with phenotypes, they do not fully reflect the complexity of human cancers. Here, we describe the use of latent factor models to further dissect the stress gene signatures in a breast cancer expression dataset. The genes in these latent factors are coordinately expressed in tumors and dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 67 publications
1
43
0
Order By: Relevance
“…The projection analysis of these signatures to a breast tumor dataset (GSE69031) was performed according to our previous reports 10, 31, 49 .…”
Section: Methodsmentioning
confidence: 99%
“…The projection analysis of these signatures to a breast tumor dataset (GSE69031) was performed according to our previous reports 10, 31, 49 .…”
Section: Methodsmentioning
confidence: 99%
“…An accumulation of extracellular lactate and low pH, often called lactic acidosis (LA), is one prominent microenvironmental stress found in most solid cancer tumors 43 . Many studies have shown that LA triggers transcriptional responses, somatic alterations and phenotypic alterations 3,4,44,45 . In addition, lactate can serve as a signaling molecule to trigger HIF-1α 46 , NF-κB 47 and stemness 48 pathways to alter the signaling events and oncogenic properties of cancer cells.…”
Section: Lactatementioning
confidence: 99%
“…There is extensive cross-talk and reciprocal metabolite flow between these alternative fuels and the sensing and metabolic pathways of glucose metabolism. The importance of these pathways can be demonstrated by the DNA amplifications or significant up-regulation of many genes involved in the metabolic adaptations under stresses 44,45 . It is important to note that while lactate and acetate are well-appreciated fuels for yeast and bacteria, they were not considered viable metabolic fuels for human cells until recently.…”
Section: Scavenging Macromoleculesmentioning
confidence: 99%
“…Our approach to this problem is to extend a factor model-based approach because of its practical application in genomic studies (Lucas et al, 2006(Lucas et al, , 2009(Lucas et al, , 2010Zheng and Lucas, 2012;Ray et al, 2014). The factor analysis framework allows dimension reduction and estimation of correlation structure in the context of high-dimensional gene expression data.…”
Section: Introductionmentioning
confidence: 99%